2020
DOI: 10.1177/2331216520948410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Directional Microphone Technology in Hearing Aids on Neural Correlates of Listening and Memory Effort: An Electroencephalographic Study

Abstract: The aim of the study was to compare the effect of different spatial noise-processing algorithms in hearing aids on listening effort and memory effort on a subjective, behavioral, and neurophysiological level using electroencephalography (EEG). Two types of directional microphone (DM) technologies for spatial noise processing were chosen: one with a wide directionality (wide DM) and another with a narrower directionality (narrow DM) to accentuate the speech source. Participants with a severe hearing loss were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Increases in listening effort have also been found to negatively influence memory processes (Guang et al, 2021;Payne, et al, 2021;Piquado et al, 2012;Rabbitt, 1968Rabbitt, , 1991. However, there is evidence that these effects are offset by the presence of supportive context (e.g., McCoy et al, 2005;Gordon-Salant & Fitzgibbons, 1997;Winneke et al, 2020). For example, Gordon-Salant and Fitzgibbons (1997) presented participants with and without hearing impairments with sentences embedded in 12-talker babble background noise.…”
Section: Listening Effort and The Effects Of Context On Behavioral Measuresmentioning
confidence: 99%
“…Increases in listening effort have also been found to negatively influence memory processes (Guang et al, 2021;Payne, et al, 2021;Piquado et al, 2012;Rabbitt, 1968Rabbitt, , 1991. However, there is evidence that these effects are offset by the presence of supportive context (e.g., McCoy et al, 2005;Gordon-Salant & Fitzgibbons, 1997;Winneke et al, 2020). For example, Gordon-Salant and Fitzgibbons (1997) presented participants with and without hearing impairments with sentences embedded in 12-talker babble background noise.…”
Section: Listening Effort and The Effects Of Context On Behavioral Measuresmentioning
confidence: 99%
“…In difference images, the outer pixels of time-frequency regions showing significant differences are highlighted with white outlines alpha power suppression during the listening interval for the parietal and central occipital clusters of ICs. Though many studies have pointed to more difficult conditions showing an increase in alpha power with more difficult listening conditions (Alhanbali et al, 2019;Dimitrijevic et al, 2019;Petersen et al, 2015;Winneke et al, 2020;Wisniewski et al, 2017;Wöstmann et al, 2015Wöstmann et al, , 2017, there are a number of other studies showing greater suppression of alpha power while listening to speech in a difficult compared to an easy condition. For instance, Hauswald et al (2020) found that parietal alpha power decreased with increased degradation to sentences through vocoding (also, see Hjortkjaer et al, 2020;Hunter, 2020;Seifi Ala et al, 2020).…”
Section: F I G U R Ementioning
confidence: 99%
“…Pupillometry has also helped to identify potential solutions to excessive listening effort problems (e.g., through signal processing in hearing aids; Ohlenforst et al., 2017; Wendt et al., 2017) and has given researchers the capability to objectively measure listening effort in children who could experience developmental delays as a result of excessive effort (GĂłmez‐Merino et al., 2020). Recently, there have been a large number of studies that have used analyses of alpha‐band (~8–13 Hz) power in the M/EEG in a similar vein (Alhanbali et al., 2019; Decruy et al., 2020; Hall et al., 2019; Hunter, 2020; Marsella et al., 2017; McMahon et al., 2016; Miles et al., 2017; Obleser et al., 2012; Petersen et al., 2015; Seifi Ala et al., 2020; Winneke et al., 2020; Wöstmann et al., 2015). For the most part, alpha power recorded at parietal and occipital sensors has been stronger in difficult compared to easy conditions (e.g., Obleser et al., 2012) and has been stronger for hearing‐impaired compared to non‐impaired individuals (e.g., Petersen et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is not an issue if short stimuli are assessed after playback, but it may not be the best method when evaluating listening effort over longer listening periods such as an entire movie. Such a long-term, passive monitoring of listening effort and the potential benefit of source separation for broadcast signals could possibly be made using neurophysiological markers of cognitive load, e.g., electroencephalography (EEG) [50], pupil dilatation [51], functional near-field infrared spectroscopy (fNIRS) [52], or other physiological indices [53], [54].…”
Section: Discussionmentioning
confidence: 99%